Association of intrinsic and extrinsic motivating factors with physician burnout and job satisfaction: a nationwide cross-sectional survey in Taiwan. Issue 3 (10th March 2020) - Tung, Yu-Chi; Chou, Ying-Yi; Chang, Yu-Hsuan; Chung, Kuo-Piao
Abstract : Objective: The aim of this study was to systematically and simultaneously examine the association of intrinsic and extrinsic motivating factors with physician burnout and job dissatisfaction. Design: A nationally representative survey was fielded from September to November 2017. Setting: Hospitals and clinics throughout Taiwan. Participants: A total of 6674 physicians. Main exposure measure: The main exposure measures were intrinsic motivators (sense of calling, personally rewarding hours per day and meaningful, long-term relationships with patients) and extrinsic motivators (income, work hours, autonomy, and pay-for-performance (P4P) and bundled payment initiatives). Main outcome measures: The main outcome measures were physician burnout and job dissatisfaction. Results: A total of 1152 physicians returned the surveys. More sense of calling and personally rewarding hours per day were associated with less physician burnout (OR 0.16, 95% CI 0.10 to 0.26 and OR 0.25, 95% CI 0.13 to 0.47, respectively) and job dissatisfaction (OR 0.35, 95% CI 0.21 to 0.57 and OR 0.46, 95% CI 0.26 to 0.83, respectively). Longer work hours were associated with more physician burnout (OR 2.67, 95% CI 1.54 to 4.63) and job dissatisfaction (OR 1.71, 95% CI 1.05 to 2.79). Not receiving P4P bonuses from their organisations was associated with more physician burnout (OR 1.56, 95% CI 1.02 to 2.38). Not sharing the losses from caring for patients included in the bundled payment system was associated with less physician burnout (OR 0.59, 95% CI 0.36 to 0.97). Conclusions: Fostering a healthcare work environment that supports intrinsic motivation and improves work hours may reduce physician burnout and job dissatisfaction. Rewarding physicians fairly and equitably may prevent them from feeling burned out. Value-based care delivery and payment model innovations, such as bundled payments, may encourage healthcare professionals to coordinate care through the standardisation of care to decrease burnout.